Results of Surgical Treatment of Patients with Chronic Acromioclavicular Joint Dislocations - Bezruchenko, S.O.; Dolhopolov, O.V.; Yuriichuk, L.M.; Yarova, M.L.; Bohdan, S.V.; Siforov, D.V. (TERRA ORTHOPAEDICA, 2022)
Relevance. Treatment of chronic acromioclavicular joint dislocations remains a controversial issue and ranges from conservative treatment to extensive reconstruction.Objective: to compare clinical and radiographic results of surgical treatment of patients with chronic acromioclavicular joint dislocation.Materials and Methods. A retrospective analysis of 41 patients with chronic acromioclavicular joint dislocation was performed (time from the injury was more than 3 weeks). The patients were divided into two groups: group I (19 patients, 46.3%), which underwent arthroscopically assisted dynamic type of acromioclavicular joint dislocation stabilization with acromioclavicular and coracoclavicular ligaments augmentation, and group II (22 patients, 53.7%), which underwent fixation of acromioclavicular joint dislocation with Hook-plate and acromioclavicular and coracoclavicular ligaments augmentation. The mean age at surgery was 34.1±11.2 years (range 18-70 years). Most of the patients were males – 36 patients (87.8%). Clinical outcomes were assessed using the Oxford Shoulder Score, Constant – Murley Score, and Acromioclavicular Joint Instability Scoring System.Results. The mean Oxford Shoulder score before surgical treatment was 31.5±7.7 points and 33.3±4.2 points (p=0.347), and at the final follow-up 46±2.6 points and 46.1±1.6 points – in group I and group II, respectively. The mean Constant – Murley score before surgical treatment was 68.9±12.4 points and 69.7±14.5 points (p=0.863), and at the final follow-up 94.2±7.7 points and 96.5±3.9 points (p=0.291). The mean Acromioclavicular Joint Instability Scoring System score before surgical treatment was 31.3±9.5 points and 25.1±8.2 points (p=0.087), and at the final follow-up 79.9±16.7 points and 75.7±9.1 points (p=0.422), respectively. Concomitant intra-articular injuries of the shoulder joint were diagnosed in 68.4% of patients; the most common injuries were SLAP injury and long head of biceps tendonitis. Complications of treatment were noted in both groups, but there were no complications that would require additional reconstructive.Conclusions. Arthroscopic assisted dynamic fixation techniques or open fixation techniques with a specialized plate in combination with the reconstruction of acromioclavicular ligaments and coracoclavicular ligaments by tendon autografts provides good long-term functional results.